2021
DOI: 10.3122/jabfm.2021.03.200541
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of COVID-19 Vaccination Among Health System Personnel

Abstract: Introduction: One-third of the general public will not accept Coronavirus disease 2019 (COVID-19) vaccination but factors influencing vaccine acceptance among health care personnel (HCP) are not known. We investigated barriers and facilitators to vaccine acceptance within 3 months of regulatory approval (primary outcome) among adult employees and students at a tertiary-care, academic medical center.Methods: We used a cross-sectional survey design with multivariable logistic regression. Covariates included age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 41 publications
4
27
1
3
Order By: Relevance
“…Many studies conducted, for example, in Germany [ 37 ], Canada [ 38 ], India [ 39 ] and the USA [ 40 ] following the release of vaccines describe a vaccine acceptance level comparable with our study. However, other studies conducted in Germany [ 41 ], the United Arabic Emirates [ 42 ], Czech Republic [ 43 ] and the USA [ 44 ] reveal lower vaccine acceptance levels compared to our study.…”
Section: Discussioncontrasting
confidence: 97%
“…Many studies conducted, for example, in Germany [ 37 ], Canada [ 38 ], India [ 39 ] and the USA [ 40 ] following the release of vaccines describe a vaccine acceptance level comparable with our study. However, other studies conducted in Germany [ 41 ], the United Arabic Emirates [ 42 ], Czech Republic [ 43 ] and the USA [ 44 ] reveal lower vaccine acceptance levels compared to our study.…”
Section: Discussioncontrasting
confidence: 97%
“…The favourable risk-benefit ratio estimation was a significant and robust predictor of BD acceptance among our participants. The same finding was reported earlier among several population groups, e.g., Czech university students [70], Palestinian healthcare students [71], and American HCW [116], who were more likely to accept COVID-19 vaccine when they had favourable risk-benefit ratio assessment. This fundamental concept of an individual's risk-benefit ratio assessment has been widely used in vaccine communication and vaccine hesitancy research, as it portrays perceived effectiveness and safety of the vaccine from one side and perceived susceptibility to the infection from another side [117].…”
Section: Discussionsupporting
confidence: 86%
“…Our study showed that previous and current health perceptions did not affect COVID-19 vaccine acceptance. Similarly, other studies conducted in China by applying the SF-12 scale, and conducted in USA, no difference was encountered in the group considering vaccination and the hesitant group [11,18]. On examination of the studies evaluating the effect of having a chronic disease on vaccine acceptance, a review article examining COVID-19 vaccine hesitancy in healthcare workers, having a chronic illness was associated with a higher rate of COVID-19 vaccine acceptance [9].…”
Section: Discussionmentioning
confidence: 85%
“…In a systematic review exploring COVID-19 vaccine hesitancy in healthcare workers, direct contact/care with COVID-19 patients or higher perceived risk and fear of being infected with COVID-19 were associated with lower COVID-19 vaccination hesitancy in more than half of the studies [9]. Distinctively, another study, assessing vaccine acceptance of healthcare personnel, identified no correlation between COVID-19 vaccine acceptance and having a work role involving direct patient interaction [18]. As for our study, there was also no significant impact of working in the departments providing one-to-one care to a COVID-19 patient on the decision to have a COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation